(Z)-7, 4′-Dimethoxy-6-hydroxy-aurone-4-O-β-glucopyranoside exerts neuroprotective effects in vitro and anxiolytic activity in vivo. Issue 4 (6th March 2019) - Li, Hua; Li, Xuhui; Luo, Wei; Zhu, Xiaolong
Abstract : This study investigated the neuroprotective effects of ( Z )-7, 4′-dimethoxy-6-hydroxy-aurone-4- O - β -glucopyranoside (DHG) against hydrogen peroxide-induced cell damage in PC12 cells and further evaluated its effects on doxorubicin-induced anxiety-like behavior in rats. PC12 cells were treated with different concentrations of DHG (1–10 µM) for 24 h and then exposed to 0.2 mM hydrogen peroxide for 12 h. Cell viability was measured using the 3-(4, 5-dimethylthiazol)-2, 5-diphenyltetrazolium-bromide and lactate dehydrogenase assay. The apoptosis was detected by annexin V-PI staining. Oxidative stress was confirmed in PC12 cells by enzyme-linked immunosorbent assay, real-time PCR, and western blot. The anxiolytic effects of DHG were evaluated in the elevated plus maze test. Our results showed that DHG treatment significantly increased cell viability and decreased PC12 cell apoptosis induced by hydrogen peroxide by increasing the mitochondrial membrane potential, decreasing the cytochrome c release, inhibiting the activities of caspase-3 and caspase-9, and regulating the expression of apoptosis-related proteins. Moreover, DHG treatment effectively attenuated the redox imbalance in PC12 cells by enhancing the activity of superoxide dismutase and increasing the level of glutathione, as well as decreasing levels of malondialdehyde and intracellular reactive oxygen species. Furthermore, DHG treatment significantly mitigated the doxorubicin-induced adverse behavioral changes in rats. These results indicate the neuroprotective and antiapoptotic properties of DHG exerted by counteracting the oxidative stress and highlight DHG as a potential therapeutic regimen for behavior impairment of anxiety.